Inside Cover: Surface Enhanced Raman Scattering and Gated Materials for Sensing Applications: The Ultrasensitive Detection of Mycoplasma and Cocaine (Chem. Eur. J. 38/2016). Issue 38 (30th August 2016) - Oroval, Mar; Coronado‐Puchau, Marc; Langer, Judith; Sanz‐Ortiz, Marta Norah; Ribes, Ángela; Aznar, Elena; Coll, Carmen; Marcos, María Dolores; Sancenón, Félix; Liz‐Marzán, Luis M.; Martínez‐Máñez, Ramón
Abstract : The combination of gated materials with SERS spectroscopy produced highly sensitive and selective sensing systems. Crystal violet‐loaded mesoporous silica nanoparticles are used in combination with suitable caps and gold nanotriangles for the detection of Mycoplasma genomic DNA and cocaine. In both cases a highly selective and sensitive response is found. More information can be found in the Full Paper by L. M. Liz‐Marzán, R. Martínez‐Máñez et al. onpage 13488 ff.